Hey Google!: Can IPA improve L2 Learners' Willingness to Communicate? - Priyanto, Rian Adi; Ramadan, Nisrina Fauziah (English Education: Jurnal Tadris Bahasa Inggris, 2023)
The willingness and determination to engage in communication can result in real communication actions, which, in turn, contribute to improved oral proficiency. As digital media and communication technologies continue to advance rapidly, EFL students are becoming more engaged in practising English through various digital platforms. Recent research has been conducted to examine the connection between second language willingness to communicate (L2 WTC) and these digital language learning experiences. The recent study aims to address the use of Google Assistant as an intelligent personal assistant in providing the learning and practice of speaking for EFL learners to speak English fluently. Specifically, the recent objective is to analyse the implementation of Google Assistant in enhancing their willingness to communicate in the target language.